The Role of Nature (Tabiat) in Persian Medicine - Gholamreza Kordafshari; Hoorieh Mohamadi Kenari; Esmaeil Nazem; Maryam Moghimi; Mohammad Reza Shams Ardakani; Mansoor Keshavarz; Arman Zargaran (Tehran University of Medical Sciences, 2017)
In middle and west Asia, Europe and north of Africa in ancient and medieval time the main paradigm  and doctrine of medicine was based on humoral theory. This theory of medicine was based on four temperaments (mizaj). Regarding, it was a terminology called Tabiat (Nature) in the humoral medicine which plays a key role in the paradigm as a wisdom force in the body to keep body healthy and back body to healthy condition in diseases. There were four principles of nature: Wisdom (Hikma), Cosmos, Attorney, and Treatment.  Based on the Persian medicine principles, physician is the servant of the nature. He/she should try to help the nature of the patient to restore health.